2007
DOI: 10.1186/1471-2431-7-33
|View full text |Cite
|
Sign up to set email alerts
|

A family-based education program for obesity: a three-year study

Abstract: BackgroundThe epidemic of obesity is increasing in all countries. However, the number of controlled studies focusing on childhood obesity, with a long follow-up is still limited. Even though Behavioral Therapy shows some efficacy, it requires a prolonged teamwork that is not always available in public health settings. In addition, Behavioral Therapy is not always accepted. We describe a new intensive and sustainable family-based, Therapeutic Education program for childhood obesity.MethodsControlled clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
(42 reference statements)
0
28
1
3
Order By: Relevance
“…A new study from Italy is interesting because the follow-up period was 3 years. Children (n=85) and their parents followed a Therapeutic Education Program resulting in a significant 0.44 decrease in BMI SDS over the 3-year period [41]. However, the change we found was not as large as that of a small study from the USA with severely obese children lasting for 3 months.…”
Section: Discussioncontrasting
confidence: 46%
“…A new study from Italy is interesting because the follow-up period was 3 years. Children (n=85) and their parents followed a Therapeutic Education Program resulting in a significant 0.44 decrease in BMI SDS over the 3-year period [41]. However, the change we found was not as large as that of a small study from the USA with severely obese children lasting for 3 months.…”
Section: Discussioncontrasting
confidence: 46%
“…Craeynest et al 2008;Fennig and Fennig 2006;Lazzer et al 2005), and/or education on healthy eating/nutrition (e.g. Reinehr et al 2007;Rice et al 2008;Sacher et al 2005;Tanas et al 2007) with the traffic light diet representing the most commonly prescribed diet featured in studies (e.g. Epstein et al 2001Epstein et al , 2004Jiang et al 2005;Levine et al 2001).…”
Section: Multiple Components Of Treatment Interventionsmentioning
confidence: 99%
“…14 They have also shown that a behavioral approach to changing lifestyle in children 15 or multisetting strategies 7 can produce significant and clinically meaningful weight reduction in children compared with standard care or self-help. 16 Some studies also highlight the need to pay attention to parental influence, 17 especially for younger children, 18 as parents are sometimes unconcerned about their child' s weight status 19 and they may not believe that excess weight gain can negatively affect their child' s health. 4 Expert Committee recommendations 15 suggest the use of patient-centered counseling techniques such as motivational interviewing, which helps families identify their own motivation for making changes.…”
mentioning
confidence: 99%